Bacterial meningitis in children with an abnormal craniocerebral structure - Pan, Jiali; Xu, Wei; Song, Wenliang; Zhang, Tao (Frontiers in Pediatrics, 2023)
Background We studied the causative pathogens, clinical characteristics, and outcome of bacterial meningitis in children with an abnormal craniocerebral structure. Methods A retrospective single-center study was conducted on children aged in the range of 29 days to 14 years by using data obtained from the pediatric intensive care unit in Shengjing Hospital between January 2014 and August 2021. All children were diagnosed with bacterial meningitis. They were divided into complex and simple groups by taking into account the presence of an abnormal craniocerebral structure before they contracted bacterial meningitis. We collected data on demographics, clinical presentations, laboratory results, imaging studies, treatments, and outcomes. Results A total of 207 patients were included in the study (46 in the complex group and 161 in the simple group). Patients in the complex group had a lower mortality rate (6.5% vs. 11.2%, p < 0.05), positive blood culture (13.0% vs. 34.8%; p < 0.05), multiple organ dysfunction syndrome (0% vs. 9.3%; p < 0.05), and shock (2.2% vs. 9.3%; p = 0.11). These patients were more often detected with neurological sequelae (80.4% vs. 53.4%; p < 0.05), cerebrospinal fluid drainage (50% vs. 15.5%; p < 0.05), nosocomial infection (54.3% vs. 3.1%; p < 0.05), and multidrug-resistant bacteria (62.5% vs. 55.6%, p = 0.501). In patients in the simple group, infection was mostly confined to the nervous system. Conclusion Bacterial meningitis patients with an abnormal craniocerebral structure had fewer bloodstream infections, lower mortality rates, and higher incidence rates of neurological sequelae. Pathogens were more likely to be nosocomial and multidrug-resistant bacteria.